1993
DOI: 10.1002/jbm.820271006
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethyleneimine) modified filters for the removal of leukocytes from blood

Abstract: Polyurethane membrane filters and filters coated with poly(ethyleneimine) were used to investigate the influence of leukocyte adhesion during filtration. Treatment of the filters with an aqueous solution of 1% (w/v) poly(ethyleneimine) (PEI) led to the introduction of amine groups at the filter surfaces, as was confirmed by X-ray photoelectron spectroscopy. The modification procedure did not significantly change the porous structure in the filters, as was demonstrated by SEM and porometry. Using 14C-labeled po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…In some situations, such as in blood transfusion, it is necessary to reduce the concentration of leukocytes in blood, in order to prevent leukocyte-mediated adverse effects [51,54,55]. Therefore, the materials described here may contribute to develop additional tools for the depletion of leukocytes, taking advantage of the ferromagnetic properties of nickel nanowires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some situations, such as in blood transfusion, it is necessary to reduce the concentration of leukocytes in blood, in order to prevent leukocyte-mediated adverse effects [51,54,55]. Therefore, the materials described here may contribute to develop additional tools for the depletion of leukocytes, taking advantage of the ferromagnetic properties of nickel nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, which employed leukocyte suspensions, have shown that surface modification with PEI of polyurethane films/filters improved leukocyte removal and adhesion to surfaces; however, no improvement was found when whole blood was used [51,52]. Leukocytes have a negative zeta potential [53] and therefore are prone to interact strongly with the positive surface of the NiNW.…”
Section: Resultsmentioning
confidence: 99%
“…This is important for clinical aspects because in some cases the leukocytes have to be removed from the blood. For example, in blood transfusions the concentration of leukocytes in the blood has to be reduced to prevent leukocyte-mediated adverse effects (Bruil et al, 1993;Bruil et al, 1995;Singh and Kumar, 2009 Many of the nanowires, with magnetic nanowires being no exception, are combined with Au. By introducing the Au segments that take part in the (bio)functionalization, the main and crucial step towards final applications is made.…”
Section: (Bio)chemical Functionalization Of One-segmented Magnetic Namentioning
confidence: 99%
“…The adherence of leucocytes to glass fibres has been used to remove leucocytes from blood. Several investigations have been conducted to identify natural or synthetic fibres to which leucocytes bind (Rasp et al , 1981; Lang et al , 1988; Bruil et al , 1992, 1993). Several materials have been selected for their biocompatibility or capacity to react with leucocytes and used in filters to deplete blood products of leucocytes.…”
mentioning
confidence: 99%